Optimalisasi Peningkatan Minat Baca Siswa Pada Dinas Perpustakaan Dan Kearsipan Kota Medan - Utami, Rida; Kartini, Siti Agus; Astuti, Ermayanti; Syahputra, Arman (Publikasi Pengabdian Masyarakat, 2025)
Reading is very important for human life, especially for students. Reading is a way to dig up information from something written by someone. The main purpose of reading is to gather information and understand what a reading is. The more we read, the more information we will get. Although sometimes we get the information indirectly. Reading is also an important activity because students can absorb information in a text or reading, so the habit of reading must be fostered from an early age. One way that can be used to improve reading habits is by providing interesting reading facilities such as reading interest in the Medan City Library Archives Service. The Medan City Library was established to provide access for the public to information, knowledge, and literacy. This library is a strategic information center, offering various collections of books, magazines, and digital resources to meet the increasing needs of the community for literacy. In addition, the library also plays a role in facilitating research and development, as well as supporting literacy activities and improving literacy skills.